Liquidity, Profitability, and Market Valuation: The Mediating Effect of Dividend Payout Ratio on Price Earning Ratio - Ardhan Ardiansyah Kawakibi; Kusuma Ratnawati; Fitria Ariyani (Journal of Management Research and Studies, 2026)
Financial ratios are important indicators for investors in assessing firm performance and market valuation. Price Earning Ratio is often used to evaluate the attractiveness of a company’s stock, while liquidity, profitability, and dividend policy may influence investors’ perceptions. This study aims to obtain empirical evidence regarding the effect of Cash Ratio, Return on Equity, and Dividend Payout Ratio on Price Earning Ratio, both directly and indirectly through Dividend Payout Ratio as a mediating variable. This research uses a quantitative approach with data obtained from companies listed on the Indonesia Stock Exchange. The data were analyzed using the Structural Equation Modeling method. The empirical findings show that both Cash Ratio and Return on Equity are unable to increase Dividend Payout Ratio. Cash Ratio has a positive effect on Price Earning Ratio, while Return on Equity and Dividend Payout Ratio do not affect Price Earning Ratio. Furthermore, Dividend Payout Ratio does not act as a strong mediating variable in the relationship between Cash Ratio and Price Earning Ratio, nor between Return on Equity and Price Earning Ratio.